2004
DOI: 10.1348/0144666042038006
|View full text |Cite
|
Sign up to set email alerts
|

Social support and its consequences: ‘Positive’ and ‘deficiency’ values and their implications for support and self‐esteem

Abstract: Recent research on social support has suggested that there may be only a weak correlation between perceived and received (enacted) support, with the former best seen as a stable, personality-like trait. This study investigates the relationship between individual values, self-esteem and perceived and received support, with samples taken from four nations (the UK, Portugal, Ghana and Mozambique). Respondents completed Schwartz's Portrait Values Questionnaire (Schwartz, Melech, Lehmann, Burgess, & Harris, 2001) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
55
2
6

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(73 citation statements)
references
References 45 publications
(50 reference statements)
6
55
2
6
Order By: Relevance
“…Empirical evidence in social psychology, however, has found that perceived support is more consistently related to outcome variables than received support (e.g., Cohen & Hoberman, 1983;Wethington & Kessler, 1986;Helgeson, 1993). Further, perceived and received support may, in fact, be distinct constructs that typically share as little as 20% common variance (e.g., Cohen & Hoberman, 1983;Goodwin, Costa, & Adonu, 2004;Komproe, Rijken, Ros, Winnubst, & Hart, 1997). The present study addresses the recommendation of Bianco and Eklund (2001) to incorporate measures of both perceived and received support in the same study.…”
mentioning
confidence: 78%
“…Empirical evidence in social psychology, however, has found that perceived support is more consistently related to outcome variables than received support (e.g., Cohen & Hoberman, 1983;Wethington & Kessler, 1986;Helgeson, 1993). Further, perceived and received support may, in fact, be distinct constructs that typically share as little as 20% common variance (e.g., Cohen & Hoberman, 1983;Goodwin, Costa, & Adonu, 2004;Komproe, Rijken, Ros, Winnubst, & Hart, 1997). The present study addresses the recommendation of Bianco and Eklund (2001) to incorporate measures of both perceived and received support in the same study.…”
mentioning
confidence: 78%
“…Perceived and received support are distinct constructs, typically sharing as little as 20% common variance (e.g. Cohen & Hoberman, 1983;Goodwin, Costa, & Adonu, 2004;Komproe, Rijken, Ros, Winnubst, & Hart, 1997). The distinction between perceived and received support is an important consideration for sport psychologists and coaches working with athletes.…”
Section: Introductionmentioning
confidence: 99%
“…Whilst both measures of support usually reflect an individual's perceptions of support provision, received support describes the actions actually performed by others when offering assistance. Perceived support may be best seen as a stable, individual characteristic (the perception that one is adequately supported) (Goodwin, Cost, & Adonu, 2004;Kohl & Murray, 2012). Both kinds of support are significantly correlated with self-esteem (Goodwin et al, 2004) and sport performance (Freeman & Rees, 2008), although in adult groups stronger correlations are observed with perceived support.…”
Section: Family Factorsmentioning
confidence: 99%